PERSEPSI MAHASISWA ANGKATAN 2020 PRODI PENDIDIKAN BAHASA JEPANG UNRI TERHADAP E-LEARNING MINATO SEBAGAI MULTIMEDIA PEMBELAJARAN - Sucitra, Isnaini; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This research is a quantitative descriptive study which aims todetermine the perceptions of class 2020 students regarding the use of E-LearningMinato. The population and sample in this research are all students from the class of2020, totaling 25 students. The instrument used in this research was a questionnaireconsisting of 26 statements. Based on the results of the questionnaire analysis, it isknown that the use of E-Learning Minato includes 7 principles, namely multimediaprinciples, spatial proximity principles, temporal proximity principles, coherenceprinciples, modality principles, signaling principles, and interactivity principles.Keywords: Perception, E-Learning Minato, Multimedia Learning